Macroeconomic Vulnerabilities Stemming from the Global Economic Crisis : The Case of Swaziland - Basdevant, Olivier (Departmental Papers; Departmental Paper, 2011)
Swaziland has faced a significant fiscal crisis since 2010, in the wake of loss of transfers from the Southern African Customs Union (SACU). The fiscal crisis has led to increasing vulnerabilities, not only of public finances but also on commercial banks and the private sector. This paper provides an analysis of Swaziland's main macroeconomic vulnerabilities and the main policy implications of the analysis.